2020
DOI: 10.18632/aging.103601
|View full text |Cite
|
Sign up to set email alerts
|

PDIA3 correlates with clinical malignant features and immune signature in human gliomas

Abstract: Since therapeutic strategies are limited in gliomas, new molecules or biomarkers are essential for diagnosis and therapy. Here, we investigated expression of protein disulfide isomerase family A member 3 (PDIA3) in gliomas to evaluate its potential as a promising immune target or biomarker. Transcriptome level, genomic profiles and its association with clinical practice from TCGA and CGGA databases were analyzed. All statistical analyses were performed using R project. In gliomas with high PDIA3 expression, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…In this study, we retrieved and downloaded 787 ER stress-related genes from the GeneCards website. Among them, 190 survival- 61 and DNM1L plays a regulatory role in the immune response of NKT cells to tumours. 62 The role of SHISA5 and SLN in cancers has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we retrieved and downloaded 787 ER stress-related genes from the GeneCards website. Among them, 190 survival- 61 and DNM1L plays a regulatory role in the immune response of NKT cells to tumours. 62 The role of SHISA5 and SLN in cancers has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…System. Differential expressional genes (909 DEGs in total; the screen criteria was 0.677, which was automatically calculated by considering the mean and standard deviation of logFC) between clusters 1 and 2 were identified with P packages "limma" [29,30]. log FC � mean(|log FC|) + 2 * sd(|log FC).…”
Section: Construction Of the Scoringmentioning
confidence: 99%
“…e GO and KEGG analyses were analyzed by conducting the GSVA and the GSEA analysis, respectively [32,33].…”
Section: Potential Mechanisms Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy, represented by anti-PD-1 therapy, has been regarded as a promising therapeutic option in melanoma and urothelial cancer (37)(38)(39)(40)(41). So far, clinical trials of immunotherapy have not demonstrated satisfactory results in glioma patients.…”
Section: Discussionmentioning
confidence: 99%